2007
DOI: 10.1177/001440290707400102
|View full text |Cite
|
Sign up to set email alerts
|

Repeated Reading versus Continuous Reading: Influences on Reading Fluency and Comprehension

Abstract: In this research we evaluated two methods to improve the reading fluency of struggling readers. Poor readers in Grades 2 and 4 with ( n = 17) and without ( n = 20) learning disabilities were randomly assigned to one of two fluency practice variations or to a control group. Students in the treatments practiced reading aloud under repeated or continuous reading conditions with an adult listener in 15-min sessions, 3 days per week for 14 weeks. For students in the treatment conditions, growth curve analyses revea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
107
2
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 79 publications
(116 citation statements)
references
References 33 publications
5
107
2
2
Order By: Relevance
“…We also looked at the development of general reading fluency skills, as on the basis of previous studies on tutoring programs (Baker et al, 2000;Kuhn & Stahl, 2003;O'Connor et al, 2007;Shany & Biemiller, 1995), paired reading practice could be associated with an improvement in global reading fluency tasks. In the present study, it was found that, after book reading practice for approximately 6 weeks (25 sessions), the participants in the paired reading group improved their reading speed of words more rapidly than the computer group.…”
Section: Test Sessionmentioning
confidence: 99%
See 4 more Smart Citations
“…We also looked at the development of general reading fluency skills, as on the basis of previous studies on tutoring programs (Baker et al, 2000;Kuhn & Stahl, 2003;O'Connor et al, 2007;Shany & Biemiller, 1995), paired reading practice could be associated with an improvement in global reading fluency tasks. In the present study, it was found that, after book reading practice for approximately 6 weeks (25 sessions), the participants in the paired reading group improved their reading speed of words more rapidly than the computer group.…”
Section: Test Sessionmentioning
confidence: 99%
“…Thus, the results confirm the previous findings of the positive outcomes of tutoring programs on reading fluency. Furthermore, Baker et al (2000) and O'Connor et al (2007) used tutored reading practice with limited tutor training and found gains in reading fluency and comprehension. This positive finding of tutored reading practice applies also for the children with reading deficits in a language with a regular orthography whose main problem is slow reading speed.…”
Section: Test Sessionmentioning
confidence: 99%
See 3 more Smart Citations